1989
DOI: 10.1093/jn/119.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Juvenile White Sturgeon (Acipenser transmontanus) to Utilize Different Carbohydrate Sources

Abstract: Juvenile white sturgeon were fed isonitrogenous diets containing 27.2% glucose, fructose, maltose, sucrose, lactose, dextrin, raw corn starch or cellulose for 8 wk. Growth, body composition, plasma chemistry (with the exception of glucose), and liver glucose-6-phosphate dehydrogenase (G6PDH, EC 1.1.1.49), malic enzyme (EC 1.1.1.40) and isocitrate dehydrogenase (ICDH, 1.1.1.42) activities of sturgeon were significantly (P less than 0.05) affected by the different dietary carbohydrate sources. Sturgeon fed eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
86
3
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 23 publications
13
86
3
1
Order By: Relevance
“…The higher growth performance in sturgeon fed the starch than glucose diet within the CF or MF groups may have been partly the result of the better water stability of the starch than glucose diets. The better utilization of starch than glucose diets by sturgeon, however, did not agree with our previous study (Hung et al, 1989) which showed no difference in body weight increase between sturgeon fed glucose and starch diets. This difference may have resulted from the differences in dietary protein levels and sources, diet formulations, fish sizes and feeding rates between the studies.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…The higher growth performance in sturgeon fed the starch than glucose diet within the CF or MF groups may have been partly the result of the better water stability of the starch than glucose diets. The better utilization of starch than glucose diets by sturgeon, however, did not agree with our previous study (Hung et al, 1989) which showed no difference in body weight increase between sturgeon fed glucose and starch diets. This difference may have resulted from the differences in dietary protein levels and sources, diet formulations, fish sizes and feeding rates between the studies.…”
Section: Discussioncontrasting
confidence: 93%
“…The compromised experimental conditions in the present study deviated from conditions in our previous studies (Hung et al, 1989;Shiau and Lin, 1993). This made comparing present with previous results difficult.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations